Depression and Incident HIV in Adolescent Girls and Young Women in HIV Prevention Trials Network 068: Targets for Prevention and Mediating Factors. Issue 5 (29th October 2019) - Goin, Dana E; Pearson, Rebecca M; Craske, Michelle G; Stein, Alan; Pettifor, Audrey; Lippman, Sheri A; Kahn, Kathleen; Neilands, Torsten B; Hamilton, Erica L; Selin, Amanda; MacPhail, Catherine; Wagner, Ryan G; et al.
Abstract: The human immunodeficiency virus (HIV) epidemic among adolescent girls and young women (AGYW) in sub-Saharan Africa is a critical public health problem. We assessed whether depressive symptoms in AGYW were longitudinally associated with incident HIV, and identified potential social and behavioral mediators. Data came from a randomized trial of a cash transfer conditional on school attendance among AGYW (ages 13–21 years) in rural Mpumalanga Province, South Africa, during 2011–2017. We estimated the relationship between depressive symptoms and cumulative HIV incidence using a linear probability model, and we assessed mediation using inverse odds ratio weighting. Inference was calculated using the nonparametric bootstrap. AGYW with depressive symptoms had higher cumulative incidence of HIV compared with those without (risk difference = 3.5, 95% confidence interval (CI): 0.1, 7.0). The strongest individual mediators of this association were parental monitoring and involvement (indirect effect = 1.6, 95% CI: 0.0, 3.3) and reporting a partner would hit her if she asked him to wear a condom (indirect effect = 1.5, 95% CI: –0.3, 3.3). All mediators jointly explained two-thirds (indirect effect = 2.4, 95% CI: 0.2, 4.5) of the association between depressive symptoms and HIV incidence. Interventions addressing mental health might reduce risk of acquiring HIV among AGYW.